Earthworms as catalysts in the formation and stabilization of soil microbial necromass. (11th May 2022) - Angst, Gerrit; Frouz, Jan; van Groenigen, Jan Willem; Scheu, Stefan; Kögel‐Knabner, Ingrid; Eisenhauer, Nico
Abstract: Microbial necromass is a central component of soil organic matter (SOM), whose management may be essential in mitigating atmospheric CO2 concentrations and climate change. Current consensus regards the magnitude of microbial necromass production to be heavily dependent on the carbon use efficiency of microorganisms, which is strongly influenced by the quality of the organic matter inputs these organisms feed on. However, recent concepts neglect agents relevant in many soils: earthworms. We argue that the activity of earthworms accelerates the formation of microbial necromass stabilized in aggregates and organo‐mineral associations and reduces the relevance of the quality of pre‐existing organic matter in this process. Earthworms achieve this through the creation of transient hotspots (casts) characterized by elevated contents of bioavailable substrate and the efficient build‐up and quick turnover of microbial biomass, thus converting SOM not mineralized in this process into a state more resistant against external disturbances, such as climate change. Promoting the abundance of earthworms may, therefore, be considered a central component of management strategies that aim to accelerate the formation of stabilized microbial necromass in wide locations of the soil commonly not considered hotspots of microbial SOM formation. Abstract : We argue that the activity of earthworms accelerates the formation of microbial necromass stabilized in aggregates and organo‐mineral associations and reduces the relevance of the quality of pre‐existing organic matter in this process. Earthworms create transient hotspots (casts) characterized by elevated contents of bioavailable substrate and the efficient build‐up and quick turnover of microbial biomass, thus converting SOM not mineralized in this process into a state more resistant against disturbances. Promoting earthworm abundance may be considered a strategy to accelerate the formation of stabilized microbial necromass in wide locations of the soil commonly not considered hotspots of microbial SOM formation.